2011
DOI: 10.1042/cbi20100406
|View full text |Cite
|
Sign up to set email alerts
|

Low-serum culture system improves the adipogenic ability of visceral adipose tissue-derived stromal cells

Abstract: In obese adipose tissue, infiltrating macrophages release proinflammatory cytokines that trigger insulin resistance. An adipocyte-based platform from visceral fat would be useful to elucidate the pathology of adipose inflammation and to develop therapeutic drugs for insulin resistance. ADSCs (adipose tissue-derived mesenchymal stromal cells) expanded from subcutaneous fat are intensively studied as sources for regenerative medicine. However, the adipocyte culture system from visceral fat tissue has not been ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Hauner's group showed that serum is not required for survival of human preadipocytes during adipogenesis and exposure to serum actually inhibits differentiation (9,14,25), and we confirm these results herein. When our modified 7d‐induction protocol along with well‐differentiating preadipocytes were used, up to 3% FBS did not significantly affect adipogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Hauner's group showed that serum is not required for survival of human preadipocytes during adipogenesis and exposure to serum actually inhibits differentiation (9,14,25), and we confirm these results herein. When our modified 7d‐induction protocol along with well‐differentiating preadipocytes were used, up to 3% FBS did not significantly affect adipogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…ADSCs are also a convenient source because of their high proliferation and easy maintenance. 1 × 10 8 ADSCs can be expanded to 10 g of rat epididymal fat pads or human omental fat pads over five passages [42]. Therefore, in the clinical setting, ADSCs could be considered more profitable than BM-MSCs [17].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the outcomes of longer experiments examining the effects of leptin on collagen synthesis and mineralization may be altered by the choice of low serum conditions. Low serum (2%) conditions have been shown to be beneficial for adipogenic differentiation [15] and are detrimental for osteoblast differentiation in general. Ideally, an experiment should examine osteoblast proliferation, differentiation and apoptosis with varying concentrations of leptin, and low and high serum conditions.…”
Section: Contradictory Results From In Vitro Studiesmentioning
confidence: 99%